Experimental research into aerodynamic parameters of a cylindrical one-level 8-channel cyclone - Venckus, Žilvinas; Venslovas, Albertas; Pranskevičius, Mantas (Journal of Environmental Engineering and Landscape Management, 2014)
The Environmental Protection Laboratory of Vilnius Gediminas Technical University has developed and installed a one-level 8-channel cyclone with different internal structure, which is used for separation of particulate matter from air streams. Airflow velocity was measured in five points of each channel: at the end and the beginning of the channel, in the middle of the channel and in points arranged at 45° angle from the channel’s end and beginning. The highest airflow velocity determined in 8-channel device by regulating volumes of peripheral and transit airflows with curvilinear semi-rings was in cyclone’s channel 1, while the lowest – in channel 2. Contrary to the above, the highest airflow velocity in 8-channel cyclone by using quarter-rings without holes and with 5° opening angle of plates in holes was recorded in channel 2. Tests on aerodynamic resistance were carried out in airflow inlet and outlet ducts. In all cases analysed the highest aerodynamic resistance in 8-channel cyclone was determined when airflow distribution was regulated at 75/25 ratio with semi-rings. When quarter-rings without holes and with 5° opening angle of plates in holes were used, higher aerodynamic resistance in the system was created by using quarter-rings without holes, i.e. 0° opening of plates.